2021
DOI: 10.1016/j.isci.2021.103464
|View full text |Cite
|
Sign up to set email alerts
|

Progress and prospects of reversible solid oxide fuel cell materials

Abstract: Reversible solid oxide fuel cell (RSOFC) is an energy device that flexibly interchanges between electrical and chemical energy according to people's life and production needs. The development of cell materials affects the stability and cost of the cell, but also restricts its market-oriented development. After decades of research by scientists, a lot of achievements and progress have been made on RSOFC materials. According to the composition and requirements of each component of RSOFC, this article summarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 338 publications
0
24
0
Order By: Relevance
“…This makes the task of creating high-efficiency solid oxide devices for electrochemical applications very important for now. The oxygen-and proton-conducting solid oxides may be components of various devices including fuel cells and electrolyzers [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Most well-known electrolytes for medium-temperature solid oxide fuel cells (500-700 • C) are characterized by the perovskite or perovskite-related structure ABO 3−δ [22].…”
Section: Introductionmentioning
confidence: 99%
“…This makes the task of creating high-efficiency solid oxide devices for electrochemical applications very important for now. The oxygen-and proton-conducting solid oxides may be components of various devices including fuel cells and electrolyzers [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Most well-known electrolytes for medium-temperature solid oxide fuel cells (500-700 • C) are characterized by the perovskite or perovskite-related structure ABO 3−δ [22].…”
Section: Introductionmentioning
confidence: 99%
“…Przepiórski et al ( Przepiórski et al, 2004 ) used commercial activated carbon as a raw material, fed ammonia gas at 200–1000 °C and kept it for 2 h to prepare nitrogen-doped activated carbon. The study found that the activated carbon after ammonia heat treatment has stronger CO 2 adsorption performance than commercial activated carbon, confirming the effectiveness of ammonia nitrogen incorporation; the adsorbent prepared at 400°C has the largest CO 2 adsorption capacity; The poor adsorption performance of samples activated at temperatures above 400°C may be due to the nitrogen-containing functional groups blocking the micropores or changing the pore structure ( Shen et al, 2021b ). Many scholars have studied the formation mechanism of nitrogen-containing functional groups during high-temperature ammonia treatment.…”
Section: Research Direction Of Co 2 On Porous Adso...mentioning
confidence: 86%
“…In the fuel cell mode, RSOFCs generate clean power by electrochemically converting fuels (H 2 , hydrocarbons, alcohols, etc.) with O 2 from air and function as solid oxide fuel cells (SOFCs); in the electrolysis mode, RSOFCs generate H 2 or useful chemicals by utilising excess renewable electricity and function as solid oxide electrolysis cells (SOECs) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%